A vegetation survey and mapping of the woodbush granite grassland in the Limpopo Province, South Africa - Matjie, Mapula Rose (My University, 2019)
The Woodbush Granite Grassland (WGG) is the most threatened vegetation type in Limpopo Province of South Africa. However, it has a high conservation value, because few examples of this vegetation type remain in southern Africa. Unfortunately, a large part of it is not formally conserved, making this the vegetation type most urgently in need of conservation. The study aimed at mapping transformation of the WGG, identifying species of conservation importance, and providing a management plan required for maintenance of the WGG. The objectives of the study included compiling a transformation map for the WGG, which also involved describing the remaining patches of the WGG that are in a natural or near-natural state. It also provides information on species of conservation importance, medicinal plants and threats to the WGG. On the four main study sites (Iron Crown Grassland, Haenertsburg Grassland, Ebenezer Dam Nature Reserve Grassland, and Ebenezer Dam Perimeter Grassland), quadratic plots were randomly set with a size of 25 x 25 m, and subplots of 1 x 1 m. Vegetation mapping was done during summer and winter. At each plot data was collected on all plant species occurring within the quadrat. A cover score was assigned to each plant species. A modified Braun-Blanquet data collection sheet was employed to obtain baseline data. For transformation mapping GeoTerra Image (GTI), land cover data were extracted for the WGG, using the modelled boundary as a mask, with 5 categories of transformation defined. Of the surveyed sites, the Ebenezer Dam Nature Reserve Grassland has the highest number of species, while the Haenertsburg Grassland contained the most endemic species of conservation importance. Rare species such as the Aloe zebrina, which does not occur in any formally protected area, and medicinal plants such as Athrixia phylicoides, occur on the WGG. All sites have importance with regard to WGG conservation. Identified threats include the spread of alien invasive plants, uncontrolled collection of medicinal plants, urban development, and poorly timed anthropogenic fire. vi The WGG underwent transformation to other land classes. Grassland clearing for plantations and cultivation were the main causal factors behind the observed WGG losses, with a total of 55.25% transformed. Transformation by afforestation is considered irreversible. It is concluded that the WGG is of conservation importance, and that some of it has been transformed to exotic timber plantations. The grassland is under various threats; therefore it is recommended that: (1) The proposed management plan provided in this study be adopted, (2) further research on the WGG be done on medicinal plants, (3) phytosociological and floristic studies be conducted and, (4) the effects of fire and alien invasive plant species on the grassland be investigated.
Thesis (M. Sc. (Botany)) -- University of Limpopo, 2019
Keywords: Woodbush Granite Grassland; Grassland conservation; Vegetation survey; Vegetation mapping -- South Africa -- Limpopo; Grassland conservation -- South Africa -- Limpopo; Grasslands -- South Africa -- Management